Gallbladder Agenesis - Kasi, Pashtoon Murtaza (S. Karger AG, 2011)
Gallbladder agenesis is a rare entity with an estimated incidence of 10–65 per 100,000. Females are more commonly affected (ratio 3:1), typically presenting in the 2nd or 3rd decade of life. Despite an absent gallbladder, half of patients present with symptoms similar to biliary colic, which is poorly understood. Clinicians should have a strong index of suspicion if nonvisualization is suggested by an ultrasound. HIDA scans are typically not helpful since nonvisualization of the gallbladder remains typical of cystic duct obstruction as well as of agenesis. While there are no specific guidelines for management of gallbladder agenesis, conservative management with smooth muscle relaxants is preferred. Sphincterotomy also has been reported in severe cases. Here, we report a case of a 21-year-old woman who presented with recurrent biliary colic and was diagnosed to have gallbladder agenesis on magnetic resonance cholangiopancreatography. A comparison with other cases and a review of the literature are presented.